2019
DOI: 10.1002/hep.30920
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Spectroscopy Reveals Brain Hypoxia and Cerebrovascular Dysregulation in Primary Biliary Cholangitis

Abstract: Background and Aims Primary biliary cholangitis (PBC) is an autoimmune cholestatic liver disease linked to symptoms including fatigue and altered mood/cognition, indicating that chronic liver inflammation associated with PBC can impact brain function. We employed near‐infrared spectroscopy (NIRS), a noninvasive neuroimaging technique, to determine whether patients with PBC exhibit reduced cerebral oxygen saturation (StO2) and altered patterns of microvascular cerebral blood perfusion and whether these alterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…When the hemoglobin level is low, certain conditions might happen such as hypoxia and anemia. Previous study using nearinfrared spectroscopy (NIRS) method, a noninvasive neuroimaging technique, has identified that patients with PBC demonstrated significantly reduced cerebral StO2, increased cerebral deoxygenated hemoglobin concentration, and reduced total hemoglobin (tHb) concentration compared to healthy controls [14]. Pathologically, chronic inflammation and hypoxia could induce oxidative stress by producing reactive oxygen species, while oxidative stress was associated with chronic cholangitis induce bile duct damages in PBC [15].…”
Section: Discussionmentioning
confidence: 99%
“…When the hemoglobin level is low, certain conditions might happen such as hypoxia and anemia. Previous study using nearinfrared spectroscopy (NIRS) method, a noninvasive neuroimaging technique, has identified that patients with PBC demonstrated significantly reduced cerebral StO2, increased cerebral deoxygenated hemoglobin concentration, and reduced total hemoglobin (tHb) concentration compared to healthy controls [14]. Pathologically, chronic inflammation and hypoxia could induce oxidative stress by producing reactive oxygen species, while oxidative stress was associated with chronic cholangitis induce bile duct damages in PBC [15].…”
Section: Discussionmentioning
confidence: 99%
“…Sunil et al (2012) also reported abnormal cerebral blood flow perfusion in multiple brain regions of MHE patients, and that regional cerebral blood flow in some brain regions was related to patients' cognitive impairment. Nearinfrared spectroscopy measurements of NAFLD (Takahashi et al, 2017) and PBC (Duszynski et al, 2020) patients illustrated cerebral hypoxia in these patients. Moreover, significant decreases in glucose, lactate, and tissue oxygen concentration levels were observed in the cortex of BDL-induced MHE rats (Hadjihambi et al, 2022).…”
Section: Brain Energy Metabolism Disordersmentioning
confidence: 94%
“…We have previously proposed that inflammatory responses within the brain can result in hypoxia and that this hypoxia can worsen inflammation, thereby creating a hypoxia-inflammation cycle [ 14 ]. We have also detected hypoxia in people with multiple sclerosis and primary biliary cholangitis, both conditions appearing to cause inflammation in the brain [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%